Dileme in predlog razvrstitve cannabis sativa 1. v Sloveniji - Štukelj, Roman (Dignitas (Ljubljana), 2018)
Cannabis sativa has an extremely rich history of use for various purposes. Its many thousand years of versatile usage has been tainted with stigmatization and prohibitions, which, due to various interests, began in the firs half of the last century, and peaked with the exclusion of the plant from American pharmacopoeia, stamping it in international documents. The more developed countries in the field have already found ineligibility of such prosecution. At the time of cessation of use of the plant there were some important discoveries, for example the first isolation of the active substance and the discovery of a unique biological system - endocannabinoid system. Synthetic cannabinoids have been developed in laboratories, whose efficacy and safety are not comparable to natural cannabis or its preparations. Due to a number of factors and circumstances, it is time to again correctly assess its health and social risks in the socitey to ensure its proper and updated regulations in the area. Several publicly available documents refer to positive effects of modern Cannabis sativa legislation adopted in countries where cannabis is not only adequately regulated for medical purposes but in some cases also for personal use. Besides, warnings on critial points to be addressed are important. Slovenia is at the turning point. While some individuals and civil society organizations were the ones who warned of the urgent need for change in this area in previous years, significant changes took place in 2016 also on the proffesional and political field. Experts and scientists gathered at the non-governmental International Institut for Cannabinoids ICANNA and within the working group of the Medical Chember of Slovenia. Should the use of cannabis be allowed for medical purposes is not an issue of profesional organizations. Media reports are also favourable. The political will can also be reported from unanimously adopted resolutions of the Commitee of Health of the National Assembly of the Republic of Slovenia, which ordered the Ministry of Health to prepare materials for reclassification of cannabis. In addition, regulations are being prepared to allow production and processing of cannabis in medical purposes. However, an inadequate proposal was sent to the public debate. Institute ICANNA proposed a professional re-classification of cannabis in III: group of illicit drugs, as medium and not most dangerous drug that can be used in medicine.
Keywords: cannabinoids; cannabis; classifications; Health Committee; ICANNA Institute; Inštitut ICANNA; kanabinoidi; klasifikacija; konoplja; Ministrstvo za zdravje; Ministry of Health; Odbor za zdravstvo; regulations; zakonodaja